2014
DOI: 10.1108/info-09-2013-0047
|View full text |Cite
|
Sign up to set email alerts
|

Putting things to work: social and policy challenges for the Internet of things

Abstract: Purpose – This paper aims to provide a critical assessment of the Internet of things (IoT) and the social and policy issues raised by its development. While the Internet will continue to become ever more central to everyday life and work, there is a new but complementary vision for an IoT, which will connect billions of objects – “things” like sensors, monitors, and radio-frequency identification devices – to the Internet at a scale that far outstrips use of the Internet as we know it, and will… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(133 citation statements)
references
References 21 publications
2
122
0
9
Order By: Relevance
“…The McKinsey study (Gao, Russel, & Zielke), shows that insurance companies and car owners could save $100 billion a year by reducing accidents with the help of embedded systems that detect and avoid imminent collision. The IoT will enable new business models in insurance, such as, for example, car insurance, which is based on actual usage, calculated on the basis of information obtained in real-time driving (Dutton, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The McKinsey study (Gao, Russel, & Zielke), shows that insurance companies and car owners could save $100 billion a year by reducing accidents with the help of embedded systems that detect and avoid imminent collision. The IoT will enable new business models in insurance, such as, for example, car insurance, which is based on actual usage, calculated on the basis of information obtained in real-time driving (Dutton, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Kagermann (2014) defined the IoT and the IoS as parts of the manufacturing process that has ignited the fourth industrial revolution. The IoT includes "things" and "objects" like radio-frequency identification (RFID) sensors that will send storage, processing, and analysis information, and smartphones that interact with each other and cooperate with smart components (Dutton, 2014). This leads to a new functionality of KM processes (Table 2) and involves new functionalities for CRM, customer support systems, and enterprise resource planning (ERP).…”
Section: Industry 40 and Rise Of The Iotmentioning
confidence: 99%
“…A bibliometric study of the articles published on IoT from 2000 to 2015 [20] concluded that much more research was needed that shifts the focus from purely technological to the socio-organizational implications of IoT adoption. Some work along these lines has been done in recent years in the UK [21][22][23][24][25][26] as well as several reports on many aspects of the IoT by the European Research Cluster on the Internet of Things [27]. The key social, legal and ethical issues facing the IoT, as discussed by the Oxford Internet Institute [26] In Section 3 we present a table cross-referencing the technical and business research challenges for the IoT, and the applicable mathematical tools and techniques of OR (optimization, simulation, etc.…”
Section: Research Challenges For the Future Iotmentioning
confidence: 99%
“…What is new with IoT is that it allows objects to sense, store, and communicate information in real time and thus provides new ways of doing things. However, this also triggers concerns about data sharing and privacy (Dutton, 2014). A recent study on car-related connected services indicates major regional variations in such concerns.…”
Section: Categorizing the Contextual Dynamics Of The Public Servicesmentioning
confidence: 99%